Evaluation of risk factors and biomarkers related to arterial and venous thrombotic events in idiopathic inflammatory myopathies. (3rd September 2021) - Notarnicola, A; Barsotti, S; Näsman, L; Tang, Q; Holmqvist, M; Lundberg, IE; Antovic, A
Abstract : Objectives : This study aimed to assess the contribution of traditional/disease-related risk factors and biomarkers linked to arterial and venous thrombotic events (TEs) in patients with idiopathic inflammatory myopathies (IIMs). Method : The occurrence of arterial and/or venous TEs at the time of or after IIM diagnosis was retrospectively evaluated in a cohort of 253 patients with IIMs, resulting in a final population of 246 IIM patients, 51 with reported TE (cases) and 195 without a history of TE (comparators). Information on disease characteristics and traditional risk factors for arterial and venous TE (essential hypertension, diabetes, dyslipidaemia, smoking, malignancy) was retrieved. Serum levels of anti-phospholipid antibodies (aPLs) and adhesion molecules were analysed at the time of IIM diagnosis and at the time of the TE in cases. Results : One in five IIM patients (21%) had experienced a TE, arterial TE in 22 and venous TE in 29 patients, with a peak prevalence within 5 years after diagnosis. Among traditional/disease-related risk factors, only older age was associated with both arterial and venous TEs, after adjusting for other covariates. Low serum levels of e-selectin were associated with higher odds of developing a TE, without specific association with either arterial or venous TEs. Only 6% of IIM patients had aPLs, with no significant difference between cases and comparators. Conclusions : An increased risk of both venous and arterial TEs should be considered in IIM patients, particularly close to diagnosis and in elderly people. Low serum levels of e-selectin may predict TE in IIM patients, but the underlying biological mechanism is not known.